Dinamika selitev in delovne mobilnosti v urbana središča Slovenije, 2000-2011 - Drobne, Samo (Geodetski vestnik, 2013)
In this paper, the dynamics of migration and commuting into the urban centres of Slovenia in 2000-2011 is presented. The influence of the attractiveness of urban centres, the influence of the emissiveness of migration and commuting flows in the origin and the influence of the distance between origins and destinations on migration and commuting flows into the urban centres in Slovenia were analysed in a spatial interaction model. The dynamics of the parameters were analysed for the period before (2000-2007) and in the economiccrisis (2008-2011). According the Spatial Development Strategy of Slovenia, the urban centres of Slovenia were considered at four levels: national urban centres of international importance, urban centres of national significance, urban centres of inter-regional significance
Keywords: commuting; delovna mobilnost; dinamika; dynamics; migration; selitev; Slovenia; Slovenija; urban centres; urbana središča